2012
DOI: 10.1007/s00586-012-2487-5
|View full text |Cite
|
Sign up to set email alerts
|

Posterior instrumentation, anterior column reconstruction with single posterior approach for treatment of pyogenic osteomyelitis of thoracic and lumbar spine

Abstract: Purpose Surgical treatment of thoracolumbar osteomyelitis consists of radical debridement, reconstruction of anterior column either with or without posterior stabilization. The objective of present study is to evaluate a case series of patients with osteomyelitis of thoracic and lumbar spine treated by single, posterior approach with posterior instrumentation and anterior column reconstruction. Methods Seventeen patients underwent clinical and radiological evaluation pre and postoperatively with latest follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Having to use drainage during posterior debriding to reduce the recurrence rate of infection implies that debridement via the single posterior approach is not sufficient. To reduce the recurrence rate, many orthopaedists have suggested radical debridement using the posterior approach, which theoretically results in excessive removal of healthy bone. Exposing via the OLIF corridor, the lesion can be clearly viewed and debrided up to the healthy bone, which results in precise debridement without any residual lesion or excessive removal of healthy bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having to use drainage during posterior debriding to reduce the recurrence rate of infection implies that debridement via the single posterior approach is not sufficient. To reduce the recurrence rate, many orthopaedists have suggested radical debridement using the posterior approach, which theoretically results in excessive removal of healthy bone. Exposing via the OLIF corridor, the lesion can be clearly viewed and debrided up to the healthy bone, which results in precise debridement without any residual lesion or excessive removal of healthy bone.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior debridement requires more exposure to spinal tissues and structures; therefore, it is more traumatic and time consuming than anterior debridement. Gorensek et al . reported that the average blood loss during surgery and surgery time were 1150 mL and 207 min, respectively, using the single posterior approach for debridement and fusion of pyogenic osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…Their results seem to support the views that a posterior approach alone is satisfactory, using a transforaminal lumbar interbody fusion to clear the disc, and do an interbody graft, then combined with pedicle fixation [33]. The paper by Gorensek et al [9] operated upon 23 of 108 patients, indicating that nonoperative treatment is most frequently most appropriate. Because neurological indications were frequent, in their series, decompression was necessary, and they achieved excellent results using a posterior approach alone, and the implantation of cages despite the presence of infection was not attended with failure.…”
Section: Disc and Vertebral Body Infectionmentioning
confidence: 76%
“…In 2001 Stirling [6][7][8][9] using serological tests demonstrated [10] that culture of intervertebral disc material from 36 patients operated upon for severe sciatica, showed that 53 % grew Propionebacterium acnes. In the knowledge that Modic changes-bone oedema are present in only 6 % of the general population [11], but are present in 35 % of a back pain population, and the knowledge that these changes may be due to infection, Albert et al [12] asked the question whether nuclear tissue so infected led to such changes.…”
Section: Back Painmentioning
confidence: 99%
“…For this reason, it appeared sensate to extend the use of single-staged techniques to patients affected by spinal infections with minimal anterior column disruption. The combination of radical debridement and instrumentation through a single approach has, in fact, some theoretical advantages, such as reduction of blood loss, operative time and bed rest period (12,55,61,62). Von der Hoeh et al demonstrated that a single-stage operation is as effective as a 2-stage operation, but with shorter operative time and less blood loss, although a better reconstruction of the sagittal profile and less loss of reduction, not affecting the clinical outcome, was achieved in the two-stage posterior-anterior treated group (12).…”
Section: Discussionmentioning
confidence: 99%